Feasibility study on the adoption of accrual based IPSAS and its effect on government financial reporting: a case of Attorney General’s Office - Mutusva, Sidney (Midlands State University, 2017)
The research was a feasibility study on the adoption of accrual based IPSAS and its effect on government financial reporting: A case of Attorney General‘s Office. In coming up with this paper, this researcher complied related literature from various scholars and also formulated research objectives which guided this researcher. The researcher focused on the technical staff of the Attorney General ‘Office who are the accounting and finance department personnel. The researcher compiled data using questionnaires and interviewed management. Secondary data was obtained from organizational documents and other related publications. Data obtained thereof was presented using tables, bar graphs and pie charts. The main findings of the study was that current cash based IPSAS being implemented have the weaknesses that include , inconsistence in presentation and disclosure, lack of transparency and accountability, failure to match revenues and expenditures as per the accrual concept. Thus the framework merely presents a receipts and payment summary, without a full set of the requisite financial statements, which include the statement of Comprehensive Income, Statement of Financial Position, the statement of cash flows and the notes to the financial statements. The recommendations are that there should be a stepped transition from cash based IPSAS accounting, through the modified IPSAS until we adopt and implement the accrual based IPSAS